Race, ethnicity and postoperative pain in pediatric cancer patients: a single-institution retrospective study - Owusu-Agyemang, Pascal; Feng, Lei; Cata, Juan P. (Frontiers in Anesthesiology, 2023)
Background: Studies have suggested racial and ethnic-based disparities in the intensity of postoperative pain experienced by patients. The objective of this study was to compare the peak and average post-anesthesia care unit (PACU) pain intensity scores of children of non-Hispanic (NH) White race to those of children of other racial/ethnic groups. Methods: Single-institution retrospective study of children (≤ 18 years) who had undergone cancer-related surgical procedures from June 2016 through April 2022. Multivariable logistic regression was used to assess the association between race/ethnicity and the peak and average PACU pain intensity scores. Results: Of the 1009 unique patients, 74 (7.3 %) were Asian, 93 (9.2 %) were NH-Black, 310 (30.7 %) were Hispanic/Latino, 51 (5.1 %) identified as ‘Other’ race (NH-Other), and 481 (47.7 %) were NH-White. The median age (interquartile range [IQR]) was 13.7 years (IQR, 8.2 to 16.6), and 517 (51.2 %) were female. In the multivariable analysis, the association between race/ethnicity and a peak PACU pain score greater than 3 was not significant (p = 0.062 for overall effect of race). However, upon comparing the peak PACU pain scores of children of other racial/ethnic groups to NH-White children, NH-Black children were 50.1 % less likely than NH-White children to have a peak PACU pain score greater than 3 (Odds Ratio [OR], 0.499, 95 % Confidence Interval [CI], 0.304 – 0.818; p = 0.006). Patient race/ethnicity was not associated with an average PACU pain score greater than 3 (p = 0.778). In the sub-group analysis of children who had undergone orthopedic or open abdominal surgeries, the proportions of children with peak and average PACU pain scores which were greater than 3 were not significantly different across racial/ethnic groups (p = 0.250 and p = 0.661, respectively). Conclusions: In this retrospective study of children who had undergone cancer-related surgery, NH-Black children had significantly had lesser odds than NH-White children of having a peak PACU pain score of moderate or severe intensity. However, in the sub-group analysis of children who had undergone orthopedic or open abdominal procedures, peak and average PACU pain scores were not significantly different across racial/ethnic groups.